Effect of black polyethylene shade covers on the evaporation rate of agricultural reservoirs - Martinez Alvarez, V.=700 1 Baille, A.; Molina Martinez, J.M.; Gonzalez Real, M.M.
(Es, En)
ilus., 29 ref.
Keywords: EMBALSES; ALMACENAMIENTO DE AGUA; RIEGO; CUBIERTAS DE PLASTICO; EVAPORACION; ESPAÑA; COEFICIENTE DE TRANSFERENCIA DE MASAS; CONDENSACION; EFECTOS DE ESCALA; VIABILIDAD ECONOMICA